A Novel, Functional and Replicable Risk Gene Region for Alcohol Dependence Identified by Genome-Wide Association Study - Zuo, Lingjun (Public Library of Science, 2011)
Several genome-wide association studies (GWASs) reported tens of risk genes for alcohol dependence, but most of them have not been replicated or confirmed by functional studies. The present study used a GWAS to search for novel, functional and replicable risk gene regions for alcohol dependence. Associations of all top-ranked SNPs identified in a discovery sample of 681 African-American (AA) cases with alcohol dependence and 508 AA controls were retested in a primary replication sample of 1,409 European-American (EA) cases and 1,518 EA controls. The replicable associations were then subjected to secondary replication in a sample of 6,438 Australian family subjects. A functional expression quantitative trait locus (eQTL) analysis of these replicable risk SNPs was followed-up in order to explore their cis-acting regulatory effects on gene expression. We found that within a 90 Mb region around PHF3-PTP4A1 locus in AAs, a linkage disequilibrium (LD) block in PHF3-PTP4A1 formed the only peak associated with alcohol dependence at p<10(−4). Within this block, 30 SNPs associated with alcohol dependence in AAs (1.6×10(−5)≤p≤0.050) were replicated in EAs (1.3×10(−3)≤p≤0.038), and 18 of them were also replicated in Australians (1.8×10(−3)≤p≤0.048). Most of these risk SNPs had strong cis-acting regulatory effects on PHF3-PTP4A1 mRNA expression across three HapMap samples. The distributions of −log(p) values for association and functional signals throughout this LD block were highly consistent across AAs, EAs, Australians and three HapMap samples. We conclude that the PHF3-PTP4A1 region appears to harbor a causal locus for alcohol dependence, and proteins encoded by PHF3 and/or PTP4A1 might play a functional role in the disorder.